2009
DOI: 10.1002/bio.1104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2.5‐hour sumo training on serum opsonic activity

Abstract: Sumo is a traditional Japanese sport, but the effect of actual daily training on neutrophil function is unknown. We evaluated the effect of sumo training on serum opsonic activity (SOA), which is one of the main neutrophil-related functions. Seventeen male university sumo wrestlers participated in the study. Changes in anthropometric parameters, concentrations of serum immunoglobulins (IgG, IgA and IgM), complements (C3 and C4), myogenic enzymes (lactate dehydrogenase, asparate aminotransferase, alanine aminot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…In previous studies, we investigated and observed neutrophil function of athletes under various physical stresses such as different intensities, durations and environmental conditions of physical exercise (i.e., during normal and intensive training, and during matches and/or weight reduction periods), as well as different states of health and conditioning of the participants (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The results we obtained showed complex interrelationships regarding neutrophils and their various functions, although certain insights emerged about how these relationships work.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…In previous studies, we investigated and observed neutrophil function of athletes under various physical stresses such as different intensities, durations and environmental conditions of physical exercise (i.e., during normal and intensive training, and during matches and/or weight reduction periods), as well as different states of health and conditioning of the participants (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The results we obtained showed complex interrelationships regarding neutrophils and their various functions, although certain insights emerged about how these relationships work.…”
Section: Introductionmentioning
confidence: 82%
“…We previously categorized the changing patterns of neutrophil functions against different types of physical exercise and examined whether they could be used as an effective method to determine the condition of athletes. (14)(15)(16)(17)(18)(19)(20)(21)(22). We identified two patterns as follows: 1) "Normal".…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously reported that soccer practice increases leukocyte count in female athletes (7) and that leukocyte and inflammatory cytokines increase during the first and second halves of a soccer match and return to normal levels within 21 h after the match (8). We conducted studies on changes in immune functions in athletes from various competitive sports and results suggest that intensive exercise could accelerate and/or inhibit activity of reactive oxygen species (ROS) in neutrophils (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). We also showed that understanding of changes in neutrophil function of athletes in both short-and long-term periods can be an effective conditioning index to help athletes achieve optimal physical health.…”
Section: Introductionmentioning
confidence: 99%